2020
DOI: 10.3390/ijerph17155395
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Smoke and Airborne Microbial Contamination in Operating Theatres: Influence of Ventilation and Surgical Phases

Abstract: Air cleanliness is a crucial factor in operating theatres (OTs), where the health of patients and staff must be preserved by controlling air contamination. Particular attention must be paid to ultrafine particles (UFPs) size range, generated for instance by electrosurgical instruments (ESTs). OT contamination is also affected by ventilation systems, medical staff and their gowning system, staff routines, instruments, etc. This comparative study is based on experimental measurements of airborne microbial contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
(74 reference statements)
0
14
0
3
Order By: Relevance
“…One study stood out due to its investigation of upward displacement ventilation (UWD), which was compared to downward unidirectional airflow (UDF) combined with mixing ventilation. 108 This study ultimately found that the microbial contamination in operating rooms equipped with UWD averaged around 27 CFU/m 3 , as opposed to the average 1 CFU/m 3 found in UDF ORs; whether this result was statistically significant was not specified. Two of the 11 articles only reported particle concentrations as the outcome of their study.…”
Section: Empirical Studiesmentioning
confidence: 86%
See 1 more Smart Citation
“…One study stood out due to its investigation of upward displacement ventilation (UWD), which was compared to downward unidirectional airflow (UDF) combined with mixing ventilation. 108 This study ultimately found that the microbial contamination in operating rooms equipped with UWD averaged around 27 CFU/m 3 , as opposed to the average 1 CFU/m 3 found in UDF ORs; whether this result was statistically significant was not specified. Two of the 11 articles only reported particle concentrations as the outcome of their study.…”
Section: Empirical Studiesmentioning
confidence: 86%
“…Of the 46 studies on OR ventilation that were based on empirical data, 22 did not investigate LAF. 7,22,[98][99][100][101][102][103][105][106][107][108]46,109,110,53,66,70,[94][95][96][97] It is important to note that the conflicting way in which authors use the term "unidirectional airflow" may have led to an underestimate of the number of papers that investigated LAF. Some authors equate unidirectional airflow with LAF and use these terms interchangeably, while others do not; some studies explicitly differentiate between the two.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…The fabric quality of the medical team gowning systems and the covering of equipment and surgical tools (e.g., cotton vs. polyester/TNT) can deeply influence the contamination emission rate [33], and affect the final contaminant concentrations. A further limitation may result from the different type of surgical operations monitored and the use of electrosurgical tools during operations [34,35,43].…”
Section: Limitationsmentioning
confidence: 99%
“…The efficiency of a ventilation system is influenced by multiple factors, such as the position of the operating table, the operating team, the surgical lamps, the type of personnel clothing systems, the surgical equipment [18,[32][33][34][35], and the frequency of door opening. The surgical procedures [8] and the local risk assessment adopted for preventing SSI [18] also present particular relevance, as confirmed by recent studies on MAF [1,12,36,37] and P-UDAF systems [1,8,12,[38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Romano et al measured 23 the concentration during 13 real surgical operations in two operating rooms with different ventilation schemes: one operating room with an upward displacement flow (DV) with an air change rate of 19 1/h and the other, a hybrid operating room equipped with UDAF above the surgical table (air change rate of 48 1/h) in combination with mixing ventilation diffusers in the peripheral area outside the UDAF zone (9 1/h), resulting in a total air change rate of 57 1/h. The concentration of ultrafine particles in the size range of 0.02–1 µm was measured in one of four extract openings during the operations.…”
Section: Introductionmentioning
confidence: 99%